Efficacy of Tenofovir-Based Combination Therapy versus Tenofovir Monotherapy in Chronic Hepatitis B Patients Presenting with Suboptimal Responses to Pretreatment: A Meta-Analysis - Ling Chen; Xiwei Wang; Qiongfang Zhang; Jiaojiao Gong; Shasha Shen; Wenwei Yin; Huaidong Hu (Gastroenterology Research and Practice)
Background/Aims. It remains unclear whether tenofovir disoproxil fumarate- (TDF-) based combination therapy produces better outcomes than TDF monotherapy in chronic hepatitis B (CHB) patients. The aim of this study was to compare the efficacy of the two regimens by performing a meta-analysis. Methods. A comprehensive literature search was performed on the comparison of TDF-based combination therapy and monotherapy for CHB patients in the PubMed, Embase, Web of Science, and the Cochrane Libraries. Both dichotomous and continuous variables were extracted and pooled outcomes were expressed as risk ratio (RR) or standard mean difference (SMD). Results. Nine eligible studies (1089 subjects in total) were included in our analysis. The proportion of patients with undetectable HBV DNA at 24, 48, and 96 weeks were similar between the two comparable groups (62.5% versus 70.9%, P=0.086; 78.1% versus 83.7%, P=0.118; 86.4% versus 87.9%, P=0.626, resp.). HBV DNA reduction, rates of ALT normalization, hepatitis B e antigen (HBeAg) loss, and HBeAg seroconversion were also similar between the two groups. Conclusions. On the current data, TDF-based combination therapy seemed to be no better than those achieved by monotherapy. Further studies are needed to verify this comparison.